2012
DOI: 10.2460/javma.241.9.1169
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes toward becoming a veterinarian in a group of undergraduate agriculture and biomedical sciences students

Abstract: Considering that most students, especially males, developed their interest in veterinary medicine during grades 10 to 12, elementary school may be the best starting point for exposing students to veterinary medicine. To increase interest in large animal practice among students entering veterinary school, livestock experiences should be provided to children with no farm experience during their elementary, middle, and high school years. In our survey population, cost and duration of veterinary education had a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…This is not surprising, as one of the most commonly-recognized roles of DVMs is to support animal health and wellbeing. 24 This finding is also consistent with data from Daly and Erickson 7 , showing that 95.3% (183/192) of students enrolled in undergraduate agriculture and biomedical sciences courses indicated an enjoyment of working with animals as a major reason for wanting to pursue a career in veterinary medicine. Exposure to a particular animal or family pet was only moderately influential in students' decision to pursue a career in veterinary medicine.…”
Section: Discussion Of Substantive Findingssupporting
confidence: 81%
See 1 more Smart Citation
“…This is not surprising, as one of the most commonly-recognized roles of DVMs is to support animal health and wellbeing. 24 This finding is also consistent with data from Daly and Erickson 7 , showing that 95.3% (183/192) of students enrolled in undergraduate agriculture and biomedical sciences courses indicated an enjoyment of working with animals as a major reason for wanting to pursue a career in veterinary medicine. Exposure to a particular animal or family pet was only moderately influential in students' decision to pursue a career in veterinary medicine.…”
Section: Discussion Of Substantive Findingssupporting
confidence: 81%
“…5 Typically, the decision to become a veterinarian occurs at a rather young age and is guided by the general desire to work with animals. 6,7 Given the changing workforce needs and the current lack of diversity among applicants, it seems necessary to investigate the specific factors that influence individuals to become veterinarians. Answers to these questions could help the profession find ways to increase applicant volume, maximize the potential talent pool, find ways to market the profession to potential applicants, and identify new ways to recruit under-represented minorities.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier work by our group and others suggested that veterinary students with rural backgrounds were likely to express an intention to enter rural/food‐animal practice and/or to select food‐animal tracks during their veterinary degree, but outcome data to support this practice have not been published previously to the authors’ knowledge. Heath and Schmitz et al reported that background characteristics associated with choosing food‐animal practice on graduation included growing up on a working farm or ranch, having parents who owned livestock, growing up in a town with a population < 10,000 and having a primary interest at the time of starting veterinary studies in food‐animal or mixed veterinary practice.…”
Section: Discussionmentioning
confidence: 79%
“…11,20 It is possible Figure 3: Ratings assigned by (a) female and (b) male students from the early, mid-, and senior stages of study to the importance of understanding perspectives on welfare on their first day in practice (1 ¼ extremely important, 10 ¼ least important) that students identified these ''practical'' topics as ''competences,'' and linking importance of various topics to Day One Competences may have contributed to a bias toward ranking triage and professional ethics more highly. The more practical topics-in particular triage; professional ethics, laws, and regulations; and euthanasiahave immediate AWE implications and consequences, from Day One, and therefore may have been rated more highly.…”
Section: Discussionmentioning
confidence: 99%